Contract law at century's end: Some personal reflections - PHANG, Andrew B.L. (Institutional Knowledge at Singapore Management University, 2000)
As we approach the end of the second millennium, the common law of contract-transplanted via colonialism into many lands and climes-has indeed flourished. It has certainly developed apace in the land of its origin, England, but has also evolved in distinct directions elsewhere, particularly in Australia and New Zealand.2 But this development is simply part of a continuous process and a great many interesting issues remain to be considered at the commencement of the next millennium and beyond. This is due, in part, to the very diversity that has been briefly alluded to. However, even on a more general level, a number of issues require more definitive resolution. Indeed, both these concepts interact inasmuch as the diversity is often a reflection of the differing views held with regard to the resolution of issues on a more general level.